2019
DOI: 10.1128/mra.00187-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Salmonella enterica Serovar Enteritidis Myophage Mooltan

Abstract: Salmonella enterica serovar Enteritidis is a Gram-negative bacterium and one of the most common foodborne pathogens. Biocontrol using bacteriophage in food products or animals is one possible means by which pathogenic salmonellosis infection could be inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2 ), thus these phages are likely to recognize O:4 and O:9 O-antigens on Salmonella enterica subspecies. Indeed, it has been shown that many of these phages are able to infect Salmonella enterica belonging to both O:4 and O:9 serogroups [30] , [33] , [38] , [60] , [61] , [62] . In addition, based on the high similarity of the catalytic domains between TSP3-1 and TSP4-8 subtypes, we predict that TSPs in the TSP4-8 subtype also recognize O:4 and O:9 serogroups which have also been shown for phage SE14 [26] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 ), thus these phages are likely to recognize O:4 and O:9 O-antigens on Salmonella enterica subspecies. Indeed, it has been shown that many of these phages are able to infect Salmonella enterica belonging to both O:4 and O:9 serogroups [30] , [33] , [38] , [60] , [61] , [62] . In addition, based on the high similarity of the catalytic domains between TSP3-1 and TSP4-8 subtypes, we predict that TSPs in the TSP4-8 subtype also recognize O:4 and O:9 serogroups which have also been shown for phage SE14 [26] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2010, many more phages have been classified as Vi01-like and as of October 2023, we were able to identify a total of 150 Vi01-like phages that infect Enterobacteriaceae deposited in NCBI GenBank. Seventy of these Vi01-like phages appear in scientific articles in PubMed, primarily in genome announcements [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72...…”
Section: Introductionmentioning
confidence: 99%